(untitled) (INTERNATIONAL CONFERENCE ON ANALYSIS OF MATHEMATICS AND EXACT SCIENCES, 2024)
In this article, we analyze the importance of modern innovative pedagogues and the need for new use of communicative competence used in the educational process and student development.